Inkonsistensi Pelatihan Ekstrakurikuler Seni Tari Indang Kreasi Di SMA Negeri 1 Enam Lingkung - Zakiyah Rahmi; Susmiarti Susmiarti (Jurnal Kajian dan Penelitian Umum, 2023)
The purpose of this study is to determine and describe the Inconsistencies of Indang Dance Extracurricular Training creations at SMA Negeri 1 Enam Lingkung. This type of research is qualitative research with descriptive methods. This research instrument is the researcher himself and is assisted by supporting instruments in the form of stationery and cameras. Data collection techniques are carried out by means of literature studies, observations, interviews and documentation. The steps of analyzing data are data collection, data reduction, data presentation and conclusions. The results showed that Indang dance creation training has been carried out consistently and regularly. This Indang Kreasi dance extracurricular training is carried out four times with stages of initial or opening activities, core activities, and closing activities, including providing material about Indang Kreasi dance.Training techniques taught to students produce optimal qualities such as warming up every time they will start training activities and teaching dance movements arranged from beginning to end of the dance. As far as developments completed by understudies are dependably reliable, as far as cadence understudies can make developments as per dance music and as far as articulation understudies are additionally unconstrained in doing developments while giving lovely grins, in light of the fact that during training the mentor educator generally makes sense of the significance of development in each development made by understudies.